Hypophysentumoren - Karimian-Jazi, Kianush (Der Radiologe, 2019)
Background: In this article, the most common pituitary gland tumors and the various differential diagnoses with focus on (neuro-)radiological diagnostic criteria are presented.Materials and methodsAn intensive, selective search of the literature in PubMed was carried out. Results: Pituitary adenomas account for approximately 10-15% of all intracranial brain tumors and are the most common tumors of the sellar region. Beyond a size of 10 mm they are called macroadenomas, under 10 mm microadenomas. They can be distinguished into hormone-active and non-active adenomas. Most of the hormone-active adenomas secrete prolactin (50%), more rarely somatotropin (10%) or corticotropin (5%). Tumors in the sellar region can arise from various tissues. Due to the anatomically complex location, local adjacent structures can be affected or compressed by the tumors. Particularly in case of suprasellar extension, visual impairment due to pressure on the optic chiasm is common. Important differential diagnoses for sellar tumors include craniopharyngiomas, meningiomas, metastases, aneurysms and Rathke cleft cysts. The task of image diagnostics is the early detection of the lesions as well as the proliferation pattern into perifocal structures. Gold standard is the thin-section, contrast-enhanced MRI examination. Dynamic contrast administration is crucial for the diagnosis of the microadenoma and the specific enhancement characteristic of some other tumors.ConclusionA highly focused imaging protocol is important for the diagnosis of sellar lesions such as pituitary tumors. The current favored modality is contrast-enhanced MRI, preferably with dynamic contrast-enhanced T1-weighted sequences. Early detection of the lesions and identification of the precise anatomical location are of great importance for diagnosis and therapy.